2021
DOI: 10.3390/brainsci11091159
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Baseline on Toddler Event-Related Mu-Rhythm Modulation

Abstract: Event-related mu-rhythm activity has become a common tool for the investigation of different socio-cognitive processes in pediatric populations. The estimation of the mu-rhythm desynchronization/synchronization (mu-ERD/ERS) in a specific task is usually computed in relation to a baseline condition. In the present study, we investigated the effect that different types of baseline might have on toddler mu-ERD/ERS related to an action observation (AO) and action execution (AE) task. Specifically, we compared mu-E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In previous studies [10], [9], the optimal baseline was found to be subject-dependent, with no common preferred baseline for all subjects. Such a time-specific analysis of the ERD should be performed on our data and could confirm these inter-subject variability findings.…”
Section: Baseline Selection Variabilitymentioning
confidence: 84%
See 2 more Smart Citations
“…In previous studies [10], [9], the optimal baseline was found to be subject-dependent, with no common preferred baseline for all subjects. Such a time-specific analysis of the ERD should be performed on our data and could confirm these inter-subject variability findings.…”
Section: Baseline Selection Variabilitymentioning
confidence: 84%
“…Since ERD is a ratio, the estimation of ERD is directly related to the selection of the baseline used to compute it [3], [9]. Several studies have already shown that the selection of the nature of the baseline is significant and could affect the visualization of ERD/ERS [10], [9]. In particular, Tangwiriyasakul et al, used five different baseline movies in a motion imagery task and showed that the majority of the subjects had significantly higher mu power for particular baseline conditions, thus resulting in more pronounced mu ERD [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation